Konseling Keluarga Sebagai Strategi Pencegahan Kekerasan Dalam Rumah Tangga - Amalda (Jurnal Ilmu Bimbingan dan Konseling, 2025)
Domestic violence (DV) is a serious issue with widespread impacts on individual well-being and family stability. This article aims to examine the role of family counseling as a preventive strategy against DV using a qualitative approach and case study method. Data were collected through in-depth interviews, observations, and document analysis involving ten participants, including counselors and clients from two counseling institutions. The findings reveal that family counseling can improve communication patterns, foster empathy, and reduce the potential for violence through empowerment-based and awareness-driven interventions. Although counseling shows considerable effectiveness, challenges such as limited participation from perpetrators, social stigma, and restricted service access remain significant barriers. Therefore, family counseling needs to be strengthened as an integral part of a comprehensive protection system with cross-sectoral support. This study offers recommendations to expand counseling service access and enhance counselor capacity in the preventive handling of domestic violence.